The Blurring of Meaning in the Koplo Dangdut Song Titled "Mangku Purel" Popularized by Shepin Misa ft. Lala Widy in the Semiotic Perspective of Jhon Fiske - Retno Dwi Wahyuni; Johny Alfian Khusyairi (Jurnal Impresi Indonesia, 2025)
Along with the development of the times and increasingly rapid technology, it is possible for music artists to continue to be creative and innovate to create new genres. Like in the dangdut music genre, which began to develop koplo since the 2000s. Even today, this school is still widely favored by all circles of society, especially on the island of Java. A song can also be considered a cultural product of a region because it contains the meaning of life of the people in a certain region. Like the song "Mangku Purel," which is popular lately. Even though it is delivered using the dangdut koplo school, the song contains a deep meaning that is meant to be conveyed to the listeners. This study aims to explain the phenomenon of blurring the meaning of songs that occurs due to stage activities carried out by two singers who perform the song. The research method used was qualitative descriptive, using data in the form of screenshots that displayed the stage action of the singer when performing the song. To analyze the meaning more sharply, the researcher used a semiotic study that has been presented by Jhon Fiske at three levels, namely reality, representation, and ideology. Based on the results of the research, it can be concluded that there is a meaning of the message in the form of facts that occur in people's lives in the Koplo song.